PEREMPUAN; ANTARA NORMA DAN REALITA - Duski Samad (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Women are the pillar of state. The women have existence in dynamics of the community in the world. Throughout human history, women function and existence is not always be well and nice. Sometimes they have unwell position, seems at of Roman, Greek, Egyptian history. Some effort provides women's rights are done continually, either in the field of legal protection or religious, social and cultural. Rule of law, religious, social and cultural hardly be effective without any effort and strong will of the policy makers and all to make it happen. Keywords : Women, protection, discrimination, religion, socio culturalCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i1.65